Low-latitude conjugate ULF observation by rulfmeters - Saito, Takao; Yumoto, Kiyohumi; Seto, Masahiro; Cole, K.; Dyson, P.; Ward, J.; Gibson-Wilde, B. (1984)
P(論文) In order to identify the HM wave modes for low-latitude Pc 3 pulsations, it is important to observe ULF waves with some standardized magnetometers simultaneously at low-latitude conjugate stations. Hence, an intercontinental ULF observation was carried out from November 1982 to June 1983 at the three low-latitude stations; Onagawa (ONW), Japan, Townsville (TSV), Northern Australia, and Beveridge (BVR), Southern Australia. New ring-core type ULF magnetometers (rulfmeters) were set at the three sites. ONW (L=1.30) and TSV (L=1.29) are nearly conjugated magnetically, while ONW (38°.4) and BVR (-37°.8) are nearly at the same geographic latitude. Analyses were made to obtain various wave characteristics including polarization and orientation angle of Pc 3 ellipses, their diurnal behavior, etc. The results suggest a diurnal tendency that the low-latitude Pc 3 is due mainly to the compressional mode in 18-21 and 0-(8) UT, while the fundamental standing Alfven mode in 21-24 UT in these meridians. departmental bulletin paper